RTRWP Bali No. 16 Tahun 2009 sebagai Pedoman Penataan Ruang dan Lingkungan bagi Pembangunan Berkelanjutan - Salain, Putu Rumawan (Jurnal Kajian Bali (Journal of Bali Studies), 2012)
Abstract Environmental issue has been a prominent concern lately.Global warming has demonstrated many forms of climaticchange on earth. A notion for a green revolution is launchedto ease pressure caused by these climatic changes as well asvarious environmental degradations that inevitably take placeon a daily basis. Being part of the world community, Bali is notexcluded from these global conditions. The acceleration of Bali’sgrowth due to the increasing number of tourist visits cannotprevent changes on land utilization. Land has been treatedas a commodity. This situation has in return poisoned Bali’ssocial capital heading towards an inclining attitude favoringeconomic profits more than the tangible as well as symbolicmeanings space and the natural environment may have. A localwisdom that aims at maintaining space and its environment isdefeated by a goal to obtain financial advantages. This shift isinevitable. But how could it be controlled? In responding to thisquery, Spatial Plan for Bali No 16 Year 2009 has been instigatedto govern and manage matters relating to land uses and theenvironment. For these roles, this regulation deserves ourrespect and conformance.
Keywords: environment; land use; Spatial Plan for Bali No. 19 Year 2009